Total Quality Management as a Strategic Framework for Improving Teacher Professionalism and Student Outcome - Efrita Norman; Syamsul Anwar; Lina Marliani; Yanti Hasbian; Juliana Wahid (JUMPA : Jurnal Manajemen Pendidikan, 2026)
This study examines how Total Quality Management (TQM) functions as a strategic framework for improving teacher professionalism and student learning outcomes. Educational institutions increasingly struggle to align management practice with effective teaching and meaningful student development. The study employed a qualitative case study design at an Islamic high school to explore TQM implementation in depth. Data were collected through observation, interviews with teachers and school leaders, and document analysis, then analyzed using an interactive model of data reduction, display, and verification. The findings indicate that the transformation of teaching practice under TQM is reflected in student-centered planning, reflective teaching, and a collaborative culture among educators. TQM also strengthens teacher professionalism through continuous learning, peer collaboration, and greater accountability in teaching. The study further finds that TQM fosters student character development, particularly discipline, responsibility, and independent learning. Taken together, these three findings show that TQM operates as an integrated system linking management practice with pedagogical improvement and student development. The main implication of this study for educational management is that teacher professionalism is the decisive pathway through which quality management reaches students, so schools seeking durable improvement should invest in the professional systems that mediate quality rather than in procedural compliance alone.